A SYSTEMATIC APPROACH SUPPORTED BY ARTIFICIAL INTELLIGENCE TECHNIQUES TO SPECIFICATION STAGE IN CONCEPTUAL DESIGN OF MECHANICAL SYSTEMS - İhsan TOKTAŞ; Nizami AKTÜRK (Pamukkale University Journal of Engineering Sciences, 2002)
Conceptual design is a process progressing from a description of needs and functions to one or more abstract models, and finally to the prediction of the actual behavior and performance of the object being designed. In this paper, a methodology for the specification stage in conceptual design is presented. The specification stage provides requirements and transforms them into functions of the designed object. It occurs at the highest level of abstraction and it must provide enough information for the synthesis process where functions are transformed into design components that are further synthesized into the designed object. Methodology allows for problem solving in an active interaction with the designer. An important part of the proposed methodology is the requiremental and functional tree representing the overall logic and structure at the design problem. The methodology presented is illustrated with an example.